Vibrational biospectroscopic study and chemical structure analysis of unsaturated polyamides nanoparticles as anti–cancer polymeric nanomedicines using synchrotron radiation - Heidari, Alireza (International Journal of Advanced Chemistry, 2018)
Firstly, unsaturated polyamides nanoparticles were hardened by continuous synchrotron radiation and then, the induced changes in its chemical structure were studied by Attenuated Total Reflectionâ€“Fourier Transform Infrared (ATRâ€“FTIR) spectroscopy. It was shown that applying synchrotron radiation for hardening not only leads to reduction of hardening time but also creates cross link in polymer by breaking Carbonâ€“Carbon double bond, without any considerable change in its chemical structure. In addition, an unsaturated polyamide nanoparticle as antiâ€“cancer polymeric nanomedicines is hardened by synchrotron radiation. Its chemical structure before and after hardening is studied using Raman and Attenuated Total Reflectionâ€“Fourier Transform Infrared (ATRâ€“FTIR) spectroscopy. The results show that Raman spectroscopy is considerably better than Attenuated Total Reflectionâ€“Fourier Transform Infrared (ATRâ€“FTIR) spectroscopy in detecting the changes happened in chemical structure.Â Â